Healthy Living: Tips for Staying Regular - Linda B. Bobroff (EDIS)
Constipation means having a bowel movement fewer than three times a week. Stools are usually hard and can be painful to pass. Constipation is common among older adults. This 1-page fact sheet was written by Linda B. Bobroff and published by the UF Department of Family Youth and Community Sciences, January 2013.